OPTIMALISASI PENGAWASAN PUPUK BERSUBSIDI DI LABUHAN BADAS KABUPATEN SUMBAWA - Elly Karmeli; Vivin Fitryani; Eka Warokah (Jurnal Ekonomi & Bisnis, 2020)
This study was conducted with the aim to know the optimization of subsidized fertilizers supervision in Labuhan Badas Sub-district, Sumbawa District. Type of this study was descriptive. Type of data used was qualitative that have got through interview. The informant in this study were Head of the Agriculture Office, the head of KP3, the supervisor of the subsidized fertilizer, the agent of the distribution of subsidized fertilizers and the farmers or farmer groups which consisted of 2 people. Data analysis was done using qualitative data analysis techniques of Miles and Huberman which included data collection, data reduction, data presentation and conclusion / verification. The findings of this study showed that the distribution of fertilizers in Labuhan Badas Sub- district, Sumbawa District was in line with the process that have determined by government through the decision of the Sumbawa Regent. Optimization of distribution subsidized fertilizers supervision by KP3 in Labuhan Badas Sub- district, Sumbawa District consisted of supervision procedures and fertilizer distribution mechanisms, supervision flexibility, accuracy of distribution and modes of distorting the distribution. However, improvements were needed in the supervision procedure, namely the determination of measuring instruments, assessing, guidance to retailers and farmer groups, and evaluation of the distribution which is routinely implemented every year.